AN ANALYSIS OF STUDENTS’ LEARNING ACHIEVEMENT IN ECONOMICS AT A VOCATIONAL HIGH SCHOOL - Zul Fadly Amir; Sutrisno; Ilham Abu; Indah Permatasari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study investigates students’ learning achievement in Economics among Grade XI students at a vocational high school, where Economics functions as an adaptive subject within the curriculum. The study was motivated by preliminary observations indicating uneven achievement, particularly in calculation-based economic topics. A descriptive quantitative research design was employed, involving 68 students from the Accounting and Office Management programs selected through purposive sampling. Data were collected through documentation of students’ daily assessment scores and a diagnostic test focusing on selected Economics topics. Supporting data were obtained through classroom observations and structured interviews with the Economics teacher. Data analysis was conducted using descriptive percentage techniques by classifying students’ scores into achievement categories. The results indicate that the average learning achievement score was 76.4, categorized as “Good.” However, 22% of students did not meet the Minimum Completeness Criteria (KKM). Further analysis shows that students performed better in theoretical topics than in calculation-based materials, and Accounting students achieved higher average scores than Office Management students. These findings suggest that although overall learning achievement is satisfactory, targeted instructional strategies are required to improve students’ understanding of quantitative Economics concepts in vocational education contexts.